consumer_summary

consumer_summary - x ,p y ,I ) = x c ( p x ,p y ,V ( p x ,p...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Consumer Theory Summary “Dual” Expenditure Utility Maximization Minimization max U ( x,y ) min p x x + p y y subject to p x x + p y y I subject to U ( x,y ) U Lagrangian Lagrangian U ( x,y ) + λ ( I - p x x - p y y ) p x x + p y y + μ ( U - U ( x,y )) FONCs FONCs ∂U ∂x - λp x = ∂U ∂y - λp y = 0 μ = 1 ←----→ p x - μ ∂U ∂x = p y - μ ∂U ∂y = 0 Common SOSC - diminishing MRS Marshallian Demands Hicksian Demands x = x ( p x ,p y ,I ) x = x c ( p x ,p y ,U ) y = y ( p x ,p y ,I ) y = y c ( p x ,p y ,U ) Indirect Utility Function Expenditure Function U = V ( p x ,p y ,I ) Inverses ←----→ I = E ( p x ,p y ,U ) Roy’s Identities Shepherd’s Lemma x = - ∂V/∂p x ∂V/∂I , y = - ∂V/∂p y ∂V/∂I x c = ∂E ∂p x , y c = ∂E ∂p y | {z } x ( p
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x ,p y ,I ) = x c ( p x ,p y ,V ( p x ,p y ,I )) y ( p x ,p y ,I ) = y c ( p x ,p y ,V ( p x ,p y ,I )) x c ( p x ,p y ,U ) = x ( p x ,p y ,E ( p x ,p y ,U )) y c ( p x ,p y ,U ) = y ( p x ,p y ,E ( p x ,p y ,U )) Slutsky Equations x c p x = x p x + x x I , x c p y = x p y + y x I y c p x = y p x + x y I , y c p y = y p y + y y I...
View Full Document

Ask a homework question - tutors are online